Political Accountability In Botswana’s Liberal Democracy: A Critical Appraisal - Seabo, Batlang; Lekorwe, Mogopodi; Moseki, Kabelo (Advances in Social Sciences Research Journal, 2017)
Botswana has been regarded as a frontrunner in democratic practice and good governance, yet accountability, which is one of the cornerstones of a liberal democracy, is in a deficit. While on one hand Batswana express popular preference for accountability and demand leaders to account, on the other hand there is a short supply of accountability from elected officials and parliament. This state of affairs is at odds with modern democratic practice and is clearly indicative of an accountability deficit for a country that is considered the oldest democracy on the continent. The article argues that elected leaders and parliament should be accountable in order to enhance the quality of Botswana’s democracy.